MENULIS BERANTAI BERBANTUAN MEDIA SINIAR SPOTIFY DALAM KETERAMPILAN MENULIS TEKS CERITA FANTASI - Muhammad Ilham Safatullah; Daman Huri; Een Nurhasanah (Universitas Negeri Makassar, 2025)
This study aims to measure the effectiveness of the Spotify podcast-assisted chain writing method in improving fantasy story text writing skills among seventh grade students at SMP Negeri 4 Klari. The research used an experimental method with a nonequivalent control group design. The sample consisted of two classes, namely the experimental class, which was treated with the chain writing method assisted by Spotify podcast, and the control class, which used conventional learning methods. The data were tested through normality, homogeneity, hypothesis testing (independent sample t-test), and N-Gain Score. The results showed that the experimental class experienced a higher improvement in writing skills with an average N-Gain Score of 62.12%, compared to the control class with 34.70%. This finding is supported by the T-test with a sig value. (2-tailed) 0.000 < 0.05, which shows the application of the chain method assisted by Spotify playlist media is able to captivate students' writing appeal.